2022
DOI: 10.3390/jcm11071851
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Dilemmas with Regard to Elderly Patients with Hip Fracture: The Problem of Nonagenarians and Centenarians

Abstract: Hip fracture is the most feared complication of osteoporosis, producing up to 30% mortality at the first year. With the aging of society, it is increasingly common to deal with ethical dilemmas that involve decision making in the elderly patient with a hip fracture. The objectives of the present work are to describe the main bioethical dilemmas in this group of patients and their relationship with surgical delay. We conducted a retrospective descriptive study that studied an elderly population admitted to a Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The involvement of geriatricians in this decision-making process is crucial in the very elderly, as is taking into consideration the patient’s rights and wishes. 33 Furthermore, the multidisciplinary team should work to minimize surgery time, optimize the patient prior to surgery, mobilize the patient early and prevent postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of geriatricians in this decision-making process is crucial in the very elderly, as is taking into consideration the patient’s rights and wishes. 33 Furthermore, the multidisciplinary team should work to minimize surgery time, optimize the patient prior to surgery, mobilize the patient early and prevent postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…The sensory qualities of set dahi were evaluated in the study, including colour and appearance, flavour, body and texture, and overall acceptance. The sensory evaluation tool used a nine-category hedonic grading system: dislike extremely (1), dislike very much (2), dislike moderately (3), slightly dislike (4), neither like nor dislike (5), slightly like (6), moderately like (7), like very much (8), and extremely like (9).…”
Section: Sensory Analysismentioning
confidence: 99%
“…At present, there is a lack of agreement concerning the most effective approach to treating individuals aged 90 and above who have suffered a hip fracture. Surgeons and patients are often hesitant to proceed with surgery due to concerns over advanced age and pre-existing comorbidities that may lead to postoperative complications and mortality 9 , 10 . While certain experts 11 , 12 particularly regarding the survival results, have indicated advantages, there is concern 13 17 among certain research that high proportion of complication rates after surgery were observed whether they had been treated surgically or conservatively.…”
Section: Introductionmentioning
confidence: 99%